2008
DOI: 10.1016/j.vaccine.2007.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric coronavirus-like particles carrying severe acute respiratory syndrome coronavirus (SCoV) S protein protect mice against challenge with SCoV

Abstract: We tested the efficacy of coronavirus-like particles (VLPs) for protecting mice against severe acute respiratory syndrome coronavirus (SCoV) infection. Coexpression of SCoV S protein and E, M and N proteins of mouse hepatitis virus in 293T or CHO cells resulted in the efficient production of chimeric VLPs carrying SCoV S protein. Balb/c mice inoculated with a mixture of chimeric VLPs and alum twice at an interval of four weeks were protected from SCoV challenge, as indicated by the absence of infectious virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 79 publications
(106 reference statements)
1
75
0
Order By: Relevance
“…Recent reports have shown that the S protein may provide protective effects against SARS-CoV infection (Bai et al, 2008;Chou et al, 2005;Du et al, 2008;He et al, 2004;Lokugamage et al, 2008;Zeng et al, 2004). However, S2 shows sequence homology with selfantigens and the potential pathogenic role of the cross-reactivity of anti-S2 remains a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the S protein may provide protective effects against SARS-CoV infection (Bai et al, 2008;Chou et al, 2005;Du et al, 2008;He et al, 2004;Lokugamage et al, 2008;Zeng et al, 2004). However, S2 shows sequence homology with selfantigens and the potential pathogenic role of the cross-reactivity of anti-S2 remains a concern.…”
Section: Discussionmentioning
confidence: 99%
“…However, an early concern for application of a SARS-CoV vaccine was the experience with animal coronavirus vaccines, which induced enhanced disease and immunopathology in animals when challenged with infectious virus [96]. Indeed, a similar immunopathologic reaction has been described in mice vaccinated with a SARS-CoV vaccine and subsequently challenged with SARS-CoV [97,98,99,100,101]. Thus, safety concerns related to effectiveness and safety for vaccinated persons, especially if exposed to other coronaviruses, should be carefully examined.…”
Section: Epidemiology and Impact Of Coronaviruses In Human Healthmentioning
confidence: 99%
“…Subunit vaccines are more appealing because it was found that the inactivated whole SARS‐CoV used as a vaccine resulted in enhanced lung immunopathology when vaccinated animals were challenged with SARS‐CoV . This was attributed to the presence of N‐specific antibodies rather than S‐specific antibodies; therefore, using the whole S antigen in a vaccine could be as safe as using minimum RBD.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 99%